EURHEO: the Erasmus Mundus Master in Engineering Rheology - Hilliou, L. (2011)
EURHEO (www.eurheo.eu) is a two-year Master course delivered under the prestigious Erasmus Mundus programme. EURHEO aims at offering a pioneer advanced education programme on Rheology and its applications to different Engineering areas. It combines the expertise of six leading European Universities in the field of Rheology (University of Minho (UM - Portugal), the University of Ljubljana (ULJ - Slovenia), the Universidad de Huelva (UHU - Spain), the Kaholieke Universiteit Leuven (KUL - Belgium), the Université catholique de Louvain (UCL - Belgium) and the University of Calabria (UCAL - Italy)) and the syllabus is designed to provide students with the necessary competences to understand the relevance of Rheology in Materials Science and Engineering and apply the knowledge gained in solving real-world Engineering problems both autonomously and included in multidisciplinary research teams. We will present the EURHEO education programme, and the types of grants that Portuguese and Spanish students can apply for. The first scientific EURHEO outputs, namely results from selected Master theses, will be presented in 2 posters which report the research carried out by 2 students at UM.